Economic and Mathematical Analysis of Leasing Efficiency Evaluation for a Lessor (Global Journal of Management and Business Research, 2024)
The article examines the analysis of the conditions under which the economic activity of a leasing company as a necessary link in the current crisis between manufacturers of modern equipment and enterprises operating on the market using it is cost-effective Since the lessor can simultaneously act both as a lessee or buyer of equipment from the manufacturer on the one hand and as a lessor of this equipment for the user enterprise on the other hand the analysis of the effectiveness of its activities was carried out in the form of an assessment of the effectiveness of financial inflows and outflows of the lessee and the lessor An economic and mathematical analysis of the reduced net income of the lessor was carried out for four options for such a project two options when the lessor acts as a tenant and a lessor as well as a buyer and a lessor when using equity capital and two similar options when using a loan Analytical indicators of project effectiveness - reduced net income and profitability index - are supplemented by the payback period indicator for the calculation of which in practice a laborious recursive-logical procedure is used To obtain an analytical expression for the payback period an original technique was used based on the replacement of a discrete stream of payments with a financially equivalent continuous stream
Keywords: leasing; lessor; net present value; discounted payback period